Penguasaan Gerak Dasar Lokomotor Lari Melalui Permainan Run Game pada Peserta Didik SDN Keraton 1 Martapura - Nur Syifa; Mita Erliana; Perdinanto; Kuncoro Darumoyo (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aims to determine the level of mastery of basic locomotor running movements among students at SDN Keraton 1 Martapura, as assessed from the perspective of running technique, following the implementation of the Run Game. The study employed a descriptive quantitative approach with a pre-experimental design that adopted a one-shot case study format. The sample consisted of 25 students selected using purposive sampling (based on age, 10–11 years). The assessment instrument was a running technique observation sheet. Data collection involved administering the intervention followed by observation. Descriptive statistics were used for data analysis. The results of the study indicate that the mastery of basic locomotor running movements among students at SDN Keraton 1 Martapura after the implementation of the Run Game fell into the very good category (24%), the good category (44%), the fair category (28%), and the poor category (4%). The conclusion of the study indicates that the implementation of the Run Game has a positive effect on the mastery of basic locomotor running movements. This is demonstrated by the percentage of students in the >76% category (good and very good), which amounted to 68%.